Catalytic Substrate‐Selective Silylation of Primary Alcohols via Remote Functional‐Group Discrimination. Issue 18 (9th March 2022) - Hashimoto, Hisashi; Ueda, Yoshihiro; Takasu, Kiyosei; Kawabata, Takeo
Abstract: Silylation of alcohols has generally been known to take place at the sterically most accessible less‐hindered hydroxy group. Herein, the catalyst‐controlled substrate‐selective silylation of primary alcohols, in which the selectivity was controlled independently of the innate reactivity of the hydroxy group, based on the steric environment, is reported. The chain‐length‐selective silylation of 1, n‐ amino alcohol derivatives was achieved and 1, 5‐amino alcohol derivatives showed outstandingly high reactivity in the presence of analogues with a shorter or longer chain length under catalyst‐controlled conditions. A highly substrate‐selective catalytic silylation of pentanol analogues was also developed, in which the remote functionality at C(5) from the reacting hydroxy groups was effectively discriminated on silylation. Abstract : Precise molecular recognition of the substrate structure by catalyst 3 enabled substrate‐selective silylation of long‐chain primary alcohols. Silylation of A proceeded 11 times faster than that of B by recognition of a one‐carbon difference between primary alcohols A and B . Preferential silylation of A took place over that of C by a factor of 21 owing to discrimination of the remote functionality at C(5) from the reacting OH group at C(1).